Pembentukan konsep destinasi mesra pelancong : konsep berorientasikan pelancong sebagai pengguna / Ahmad Nazrin Aris Anuar, Habibah Ahmad, Hamzah Jusoh and Mohd Yusof Hussain - Ahmad, Habibah; Jusoh, Hamzah; Hussain, Mohd Yusof (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
Tourist friendly destination is a concept, which satisfies the tourists through the relationship and maximum utilization of the aspects of space, activity and product without any disturbance. It has been seen as a customer oriented concept where the tourists are regarded as the customers at the tourist friendly destination. However, studies that of such initiatives are quite limited and sector based, thus leaving a gap of knowledge and misunderstanding in the usage of the tourist friendly destination concept. Therefore, this study is a concept paper with the aim to identify the elements through tourism system approach incorporating the aspects of space, activity and product that makes up the foundation of tourist friendly destination concept. Through this study, five elements in the aspect of space, four elements in the aspect of activity and five elements in the aspect of product are found to influence the formation of tourist friendly destination, a concept where tourist is the customer. It is hoped that the stakeholder will be able to form the concept of tourist friendly destination through the elements in the aspects of space, activity and product in tourism system approach presented in this study in line with the effort to create a concept in accordance with the demand and wishes of the tourist as customers.